PENINGKATAN KOMPETENSI GURU DALAM MELAKSANAKAN PEMBELAJARAN MELALUI MONITORING EVALUASI BERKELANJUTAN - Hermawati Hermawati (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2022)
The competency of teachers at SMP Negeri 2 Muara Bungo in performing the teaching learning proccess in the classroom are still unsatisfied. That’s whythis research is aimed to describe the implementation of continous monitoring and evaluation to improve their competency. This research is included in School Action Research because all the teachers of SMP Negeri 2 Muara Bungo as the research’s subject. There are two cycles in designing the research. Each of them has the same phases : planning, doing, observing and reflecting. It used observation sheets and field note as the instrumen in collecting data. At the end of the research showed that (1) By applying continous monitoring and evaluation are able to improve 3% teacher’s competency in doing the teaching learning process from pra cycle to the first one, then incresing 8% from the first to the second cycle. (2) The implementing of continous monitoring and evaluation is also able to increase teachers’ diciplin tocome on time at school and having teaching preparation much better.